1640 Efficacy and Safety of Melatonin in Neonates. (October 2012) - Aversa, S; Marseglia, L; Arco, A; D'Angelo, G; Cusumano, E; Barberi, I; Reiter, RJ; Gitto, E
Abstract : Background and Aims: Newborns are more sensitive to oxidative stress than older infants. Melatonin, based on its properties as chronobiotic, antioxidant, or analgesic, offers perspectives of beneficial effects in neonatology. Aim of this study was to retrospectively review the efficacy and safety of melatonin administered at preterm and at term newborns in NICU. Methods: A retrospective patient record review of newborns treated with Melatonin in NICU of University of Messina (Italy) was performed. Results: 85 neonates were recruited and treated with Melatonin (5–70 mg/Kg/die) in six previously published RCT. Melatonin has been given to 55 preterm infants with RDS and 30 at term newborns (10 with sepsis, 10 with perinatal asphyxia, and 10 with surgical abdominal malformations). That has always been given intravenously except for 10 septic newborns receiving oral administration. In our studies, melatonin treatment was able to reduce the level of proinflammatory cytokines, lipid peroxidation products and clinical parameters of inflammation and sepsis, and to improve the clinical outcome in terms of reduction of bronchodysplasia in preterm infants with RDS. None adverse event has been observed in our population of newborns treated with melatonin. Conclusions: To our knowledge, studies related to the toxicity of melatonin have not uncovered evidence of toxicity in humans even when given in very high doses. Our studies confirmed the potential role of melatonin as a treatment in different neonatal pathologies and the safety of its use in neonates at relatively high doses for short term and in various formulations.